Deep inspiration breath-hold radiotherapy for left-sided breast cancer after conserving surgery: A dose reduction for organs at risk - Jaroš, Dražan; Kolarević, Goran; Savanović, Milovan; Marić, Slavica (Vojnosanitetski pregled, 2021)
Background/Aim. For patients with left-sided breast cancer, a major concern is the dose of radiation delivered to the heart, because of increased risk of exposure and consequently increased risk of major coronary events and side effects. In order to reduce the dose to the heart during breast irradiation, deep inspiration breath-hold (DIBH) technique was implemented in our institution. The aim of this retrospective study was to compare dosimetric parameters of DIBH on the heart, left anterior descending artery (LAD) and ipsilateral lung (IL), compared with free breathing (FB) technique. Methods. Twenty patients who underwent radiotherapy with DIBH at our institution were retrospectively analyzed. Two computed tomography (CT) scans were acquired for each patient, FB-CT and DIBH-CT. Plans consisted of two opposed tangential segmented beams and one direct beam with small dose contribution. Doses to the heart, LAD, and IL were assessed. Results. Dosimetric comparison between FB and DIBH for mean dose to the heart was 5.17 Gy vs. 3.68 Gy, respectively (p
Keywords: breast neoplasms; postoperative period; radiotherapy; respiration; heart; lung